The influence of social media marketing on customer knowledge management: The role of confidentiality in UAE public banks - Abdelrehim Awad; Ahmed Moustafa Aldabousi; Seham Albatal (Banks and Bank Systems)
Social media facilitates banks’ interaction with consumers and provides critical information about their behaviors and preferences. Nevertheless, given the sensitive nature of financial information, maintaining stringent confidentiality is of paramount importance. This study aims to examine the impact of social media marketing (SMM) dimensions on customer knowledge management (CKM) in UAE public banks, focusing on the moderating role of banking confidentiality. The study utilized a quantitative methodology with a correlational framework; data were collected from 283 respondents, who are active customers of First Abu Dhabi Bank, Emirates NBD, and Abu Dhabi Commercial Bank, through a structured questionnaire. These customers were surveyed to understand their interaction with social media campaigns, the information banks request from them, their willingness to share personal data, and their perceptions of safety and legal protections. The results revealed a strong positive relationship between SMM dimensions and CKM, with SMM explaining 65.9% of the variance in CKM outcomes (R² = 0.659, p < 0.01). Among the SMM dimensions, customization had the highest impact (R² = 0.766), followed by word-of-mouth (R² = 0.697) and aesthetics (R² = 0.651). Additionally, confidentiality was found to significantly enhance the effectiveness of SMM, with a moderating effect increasing explained variance by 6.5% (ΔR² = 0.065, β = 0.25, p < 0.01). These findings suggest that public banks in the UAE should integrate personalized SMM strategies with stringent confidentiality measures to optimize CKM. This approach not only enhances customer engagement but also builds trust, fostering sustainable growth in the digital era. Acknowledgements The authors are thankful to the Deanship of Graduate Studies and Scientific Research at University of Bisha for supporting this work through the Fast-Track Research Support Program.